Reconstructing Holocene centennial cooling events: synthesized temperature changes, chronology, and forcing in the Northern Hemisphere - Gorbarenko, Sergey A.; Shi, Xuefa; Liu, Yanguang; Bosin, Aleksandr A.; Vasilenko, Yuriy P.; Artemova, Antonina V.; Yanchenko, Elena A.; Zou, Jianjun; Yao, Zhengquan; Kirichenko, Ivan S. (Frontiers in Earth Science, 2024)
Numerous studies, spanning experimental, instrumental, historical, and modeled approaches, have delved into understanding climate change across the Holocene era and millennial-scale occurrences. However, the chronology and causes of centennial-scale climate events during the Holocene remain controversial. In this study, we overviewed 10 of the best-resolved and most accurately dated records detailing climate change in the Northern Hemisphere (NH) over the Holocene, obtained from different proxies across different climatic zones, and constructed a stack of temperature changes in the NH. Based on the constructed stack, we identified and categorized 15 notable Holocene centennial cooling events (HCCEs) in the NH (period with temperature decreases). To test the chronological validity of the constructed HCCEs, we compared them with the most accurately dated and highly resolved climate records during the last 3 kyr, which have been extensively investigated by the scientific community. Based on the close alignment of the outlined HCCEs with temperature records, we suggest that other HCCEs also match centennial climate cooling events over the last 10 kyr. To understand the origins of the established HCCEs, we compared them with potential climate influencing factors: total solar irradiance (TSI), explosive volcanic activity, Atlantic meridional overturning circulation (AMOC)-limited slowdowns, Intertropical Convergence Zone (ITCZ) fluctuations, and El Niño/Southern Oscillation (ENSO variability. Early Holocene HCCE 5, terminated by a prominent 8.2-ka cold event, was likely driven by the superposition of the AMOC limited slowdown, TSI minimum, and volcanic activity. The Holocene Thermal Maximum (HTM) happened between HCCEs 5 and 4a and was interrupted by HCCE 4c and 4b, coeval, with a significant southward shift of the ITCZ, likely related to cooling in the tropical zone. However, the sequence of HCCEs 3b, 3a, and 2b (over 4.53–3.42 BP), accompanied by small changes in the TSI, was likely forced by an increase in ENSO variability, leading to remarkable changes in the tropical processes and a southward shift of the ITCZ, coeval with the collapse of the Chinese Neolithic cultures and onset of the Holocene Neoglacial. Subsequent HCCEs 2a–0a were likely forced by the TSI minimum combined with the influence of ENSO and volcanism over the last 2 ka.